Willingness to change car use under a tradable driving credits scheme: A comparison between Beijing and the Netherlands - Nico Dogterom; Yue Bao; Meng Xu; Dick Ettema (Journal of Transport and Land Use)
Recent years have seen a surge of interest in the concept of tradable driving credits (TDC) as an alternative to road pricing and driving restriction measures. However, empirical research into drivers’ responses to a TDC measure is limited and even lacking for the Chinese context where the concept of TDC has attracted considerable attention. This paper reports the results of a survey that was the first to investigate drivers’ willingness to change car use under a hypothetical distance-based TDC measure in China (Beijing) and aimed to compare these results with the results of a comparative Dutch survey. We observed that willingness to change was considerably higher in Beijing than in the Netherlands and that a substantial share of Beijing car owners indicated an increase in car use. In both contexts, higher education and higher car use intensity had a positive effect on the willingness to change, whereas higher income had a negative effect. We found mixed results for household size, respondents’ car attitudes, and TDC scenario characteristics.